ANALISIS KEBUTUHAN KAYU BAKAR UNTUK PEMBAKARAN BATU BATA DI KECAMATAN RUMBAI, KOTA PEKANBARU - Insusanty, Enny; Sadjati, Emy; Ratnaningsih, Ambar Tri (Wahana Forestra: Jurnal Kehutanan, 2018)
This study aims to find out the needs of wood for brick making in Kecamatan Rumbai and to analyze the revenue and the contribution of the cost of wood fuel for brick making. The method used in this study is the survey method in the form of interviews to brick making business owners and field observation and calculate the needs of firewood and brick production. The average brick production of each factory is 65,000 bricks per 2 months with the amount of firewood required 20.5 m3 so for the year it takes 123 m3. For all existing factories in Muara Fajar village with the number of 80 factories is required bricks as much as 9,840 m3 per year. Components of fuel wood as fuel reached 34.9% of production costs with total cost of production (2 months) is Rp 11,448,750 and the profit earned by craftsmen is Rp 1,518,750.